Analisis Ergonomi Packaging Kayu Menggunakan Metode Failure Mode and Effect Analysis untuk Meminimalisir Kelelahan dan Meningkatkan Produktivitas - Wijaya, Ade Candra; Firman Ardiansyah Ekoanindiyo (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
During the wood packaging process, workers at PT. Kakimoto House Japan are exposed to ergonomic risks due to improper working postures and repetitive activities. These conditions lead to physical complaints and decreased productivity. This study aims to identify potential work failures using the Failure Mode and Effect Analysis (FMEA) method. Data were collected through observation, interviews, and the Nordic Body Map questionnaire involving three operators. Results show that operator 1 scored a high-risk level of 70, while operators 2 and 3 were categorized as moderate. The Risk Priority Number (RPN) analysis revealed that foot fatigue had the highest RPN of 336, followed by lower back pain and minor wrist injury, each with an RPN of 280. The highest productivity rate was recorded at 0.9985, and the lowest at 0.9964. Based on these findings, ergonomic improvements such as adjusting tool height, rearranging workflow, and providing active rest breaks were recommended. This study confirms that the FMEA approach is effective in designing ergonomic solutions to enhance worker comfort and productivity.